Penerapan Multidisciplinary Nursing Health Services (MNHS) dalam Meningkatkan Kemandirian Masyarakat Peduli Sehat Rohaniah dan Jasmaniah - Elfira, Eqlima; Melvia Girsang, Bina; Devi Tumanggoro, Roxsana; Nurbaiti, Nurbaiti (Poltekkes Kemenkes Surakarta, 2024)
Background: The service aims to increase community awareness of spiritual and physical health through the application of Multidisciplinary Nursing Health Services. This activity involves the collaboration of various disciplines in the field of nursing, namely medical-surgical nursing, basic nursing, maternity and pediatric nursing, and community mental nursing. In its implementation, the service team held educational activities, health checks, counselling, and healthy living skills training for the community. Methods: The methods used include direct counseling, interactive discussions, and field practices that involve the community directly. Results: The results of this activity show an increase in community knowledge and awareness of the importance of maintaining physical and mental health, as well as increased community involvement in supporting environmental health and healthy lifestyles. Conclusion: The application of multidisciplinary health services in nursing is effective in building a community that cares more about holistic health, both spiritually and physically.